Pain and satisfaction: the case of isolated COVID-19 patients of Pakistan - Haq,Wajiha; Irfan,Siddrah; Raza,Syed Hassan; Ahmed,Waqar; Alam,Mian; Wasif,Samia; Malik,Muhammad Wasif; Ahmad,Saeed (PeerJ, 2021)
Background Over 3 million people lost their lives across the globe due to the COVID-19 related pandemic. The unprecedented restrictions on mobility have imposed in the form of isolation, quarantines, and lockdowns to curb the profound effects of the pandemic and retain physical health. This study examined the relationship between various pain levels, demographic variables and patient satisfaction with COVID-19 during isolation. Methods The primary data in this study were collected from isolated patients during their isolation and treatment in a public hospital. We obtained information from patients with COVID-19 (N = 100) about their demographic characteristics, varying levels of pain, and satisfaction with the services provided during the isolation period. We computed the descriptive statistics to explain the profile of participants, ANOVA was used to find out the difference between various groups on patient satisfaction, and structural equation modeling was performed to examine the link between pain levels, demographic factors, and patient satisfaction. This analysis was performed with STATA and SmartPLS-3. Results The findings of this study ascertained that respondent’s education (Beta, β = 2.961, p = 0.003), assets such as possession of a house (β = 4.563, p = 0.000), perception of income adequacy during the lockdown (=2.299, p = 0.022), and negligence in prevention (β = 1.975, p = 0.049) significantly affects patient satisfaction during the isolation period. Moreover, satisfaction with life, physicians and medicine, income adequacy, and fear of the participants was significantly linked to the pain level (Model F-stat = 86.323, p = 0.0001). Patients who were satisfied with their treatment had significantly lower odds of having pain (OR 0.023, 95% CI [0.001–0.0452]). Patients who had enough income to meet their basic necessities were found to have significantly lower odds of having pain (OR 0.155, 95% CI [0.032–0.740]. Discussion and Conclusion We conclude that a higher level of education, low income, and living in a rented house contributes significantly to the feeling of more satisfaction with the provided services. This implies that people with more affluent backgrounds are less likely to be satisfied with the provided services as low-income and living in rented house groups are more satisfied during isolation than others. The pain level is also affected by subjective factors such as fear and satisfaction which need to be considered while doing patient management. This study can be helpful in improving the delivery of public services of isolation centers by considering various characteristics and demographic factors of patients.
Keywords: COVID-19; Isolation; Satisfaction; Fear; Pain